Antibiotic Resistance Microbial Inactivation And Lipid Extraction From Sewage Sludge For Biodiesel Production Using Supercritical Co2 Technology - Alsaedi, Alyaa Abdulhussein Kareem (2023)
Safe disposal of municipal sewage sludge (MSS) is a various environmental issue in sewage treatment plants worldwide due to its enormous volume of generation and containing hazardous substances. Consequently, utilising MSS for biodiesel production would be positive initiative to reduce environmental contamination and produce alternative energy resources. Accordingly, the main aim of this study is to evaluate a sustainable utilization of municipal sewage sludge as a potential feedstock for biodiesel production.